Showing the considered interest in the methods of appealing penal judgments - Abbas, Eman; Abdullah, Kadum (Journal of Legal Sciences, 2022)
The methods of appealing penal judgments are: it is the permission established for the parties to the case to show the defects of the ruling issued in it, and the request to the competent court to cancel it or amend it in a way that removes from its defects. Penal legislation differed in the possibility of appealing penal judgments; The Iraqi penal legislator has taken a different path in the methods of appealing penal judgments other than the path taken by most comparative penal legislation. After the advent of the Code of Criminal Procedure No. 23 of (1971), and based on the provisions relating to the methods of appeal in the aforementioned law, we find that It is distinguished from the comparative legislation by the following: First: to cancel the appeal; As one of the regular methods of appeal in penal judgments. Second: Adoption of a new path that has not been decided by comparative legislation, which is the appeal to correct the discriminatory decision. The conclusion, then, is: The methods of appealing penal judgments in Iraqi law are: the normal methods of objecting to the judgment in absentia, and the unusual methods of discrimination, correction of the discriminatory decision, retrial. On the other hand, we find that the Egyptian criminal legislator divided the methods of appealing penal judgments into normal ways. Others are unusual, and it goes without saying that the appellant must be a litigant in the case, and he has an interest in filing the appeal.